2017
DOI: 10.3389/fcimb.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Atypical Autophagy by Porcine Hemagglutinating Encephalomyelitis Virus Contributes to Viral Replication

Abstract: Autophagy is a basic biological metabolic process involving in intracellular membrane transport pathways that recycle cellular components and eliminate intracellular microorganisms within the lysosome. Autophagy also plays an important part in virus infection and propagation. However, some pathogens, including viruses, have evolved unique trick to escape or exploit autophagy. This study explores the mechanism of autophagy induction by porcine hemagglutinating encephalomyelitis virus (PHEV) in Neuro-2a cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…Most coronaviruses enter their target cells via plasma membrane fusion, a further entry mechanism is the endosomal acidic pH-dependent endocytosis [48]. Once the virus is internalized, only then does the fusion of virus with lysosomes depend on a low endosomal and lysosomal pH [49]. Following this, the S glycoprotein is cleaved into S1 and S2 subunits by endosomal proteases cathepsin B/L, with the resulting S2 subunit-mediating membrane fusion [50].…”
Section: Inhibition Of Cathepsin B/lmentioning
confidence: 99%
“…Most coronaviruses enter their target cells via plasma membrane fusion, a further entry mechanism is the endosomal acidic pH-dependent endocytosis [48]. Once the virus is internalized, only then does the fusion of virus with lysosomes depend on a low endosomal and lysosomal pH [49]. Following this, the S glycoprotein is cleaved into S1 and S2 subunits by endosomal proteases cathepsin B/L, with the resulting S2 subunit-mediating membrane fusion [50].…”
Section: Inhibition Of Cathepsin B/lmentioning
confidence: 99%
“…Porcine hemagglutinating encephalomyelitis virus (PHEV), a member of the Coronaviridae family, is a highly neurovirulent virus that spreads to the central nervous system via peripheral nerves ( 7 ). Pig is the natural host of PHEV, but the virus has been adapted to replicate in mouse and mouse neuroblastoma N2a cells (N2a cells) ( 8 ). PHEV infection induces neurite damage and neuronal death, which may be the cause of neurological symptoms ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that PHEV localized to the lysosomes and resulted in enlarged lysosomes (Fig 1a). Indeed, PHEV infection resulted in increased LAMP1 expression levels in vitro [19] and increased lysosome enlargement in vivo (Additional file 1). These results showed that PHEV infection leads directly to lysosomal dysfunction and indicated that there was a similarly pathological feature between PHE and several neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%